LncRNA NR_136400 Suppresses Cell Proliferation and Invasion by Acting as a ceRNA of TUSC5 That Is Modulated by miR-8081 in Osteosarcoma - Liyun Liu; Liyun Liu; Mingxia Zheng; Xinwei Wang; Yanzheng Gao; Qingguo Gu (Frontiers Media S.A., 2020)
Long non-coding RNAs (lncRNAs) are emerging as important regulators of the processes involved in cancer development and progression. The molecular mechanism by which lncRNAs regulate the progression of osteosarcoma has not been clearly elucidated. The role of NR_136400, which is an uncharacterized lncRNA, has not been previously reported in osteosarcoma (OS). In the present study, we demonstrated that NR_136400 was downregulated in OS cells and that its downregulation promoted OS cell proliferation, apoptosis, and invasion. NR_136400 downregulation facilitated EMT by inhibiting the expression of E-cadherin and elevating the expression of ZEB1, Snail, and fibronectin. In vivo experiments using a xenograft tumor mouse model revealed that NR_136400 downregulation promoted tumor growth in OS. Mechanistic investigations demonstrated that NR_136400 competitively bound to miR-8081 and then upregulated the protein expression of TUSC5. Taken together, a newly identified regulatory mechanism of the lncRNA NR_136400/miR-8081/TUSC5 axis was systematically studied in OS, providing a promising target for therapeutic treatment.